Screening of Antituberculosis Drugs by Thin Layer Chromatography - Mishra, P.; Durgbanshi, A.; Pawar, R.P. (Asian Journal of Chemistry, 2017)
Tuberculosis remains a major public health problem in developing countries. This work demonstrated a new, cost effective, fast and reproducible thin layer chromatographic screening method for the determination of rifampicin, isoniazid and pyrazinamide in pharmaceutical dosages. The solvent system used for the determination of these three drugs is (propanol:hexane:ethyl acetate:ammonia) (5:2:1.7:0.2 v/v) and the Rf value of rifampicin, pyrazinamide and isoniazid was 0.68, 0.74 and 0.50, respectively. The intra-day and inter-day repeatability of the developed method for retention factor showed standard deviation (SD) of approximately 0.5-1.0 %.